2019
DOI: 10.1371/journal.pone.0219939
|View full text |Cite
|
Sign up to set email alerts
|

Associations of family relationships and negative life events with depressive symptoms among Chinese adolescents: A cross-sectional study

Abstract: Objectives The main objective of this study was to explore the associations of family relationships and negative life events with depressive symptoms among Chinese adolescents. Methods A cross-sectional study of 3081 middle school students was conducted in Ganzhou City, Jiangxi Province, China. Students were asked to complete questionnaires regarding family relationships, negative life events, and depressive symptoms. A mediation analysis was carried out using a multipl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 61 publications
1
15
0
1
Order By: Relevance
“…Studies also focused on the social determinants of (mental) health; these are the conditions in which people are born, live, learn, work, play, and age, and have a significant influence on wellbeing [ 291 ]. Factors such as age, social or socioeconomic status, social support, financial strain and deprivation, food insecurity, education, employment status, living arrangements, marital status, race, childhood conflict and bullying, violent crime exposure, abuse, discrimination, (self)-stigma, ethnicity and migrant status, working conditions, adverse or significant life events, illiteracy or health literacy, environmental events, job strain, and the built environment have been linked to depression, among others [ 52 , 133 , 235 , 236 , 239 , 252 , 269 , 280 , 292 , 293 , 294 , 295 , 296 , 297 , 298 , 299 , 300 , 301 , 302 , 303 , 304 , 305 , 306 , 307 , 308 , 309 , 310 , 311 , 312 , 313 , 314 , 315 , 316 , 317 , 318 , 319 , 320 , 321 , 322 , 323 , 324 , 325 , 326 ,…”
Section: Resultsmentioning
confidence: 99%
“…Studies also focused on the social determinants of (mental) health; these are the conditions in which people are born, live, learn, work, play, and age, and have a significant influence on wellbeing [ 291 ]. Factors such as age, social or socioeconomic status, social support, financial strain and deprivation, food insecurity, education, employment status, living arrangements, marital status, race, childhood conflict and bullying, violent crime exposure, abuse, discrimination, (self)-stigma, ethnicity and migrant status, working conditions, adverse or significant life events, illiteracy or health literacy, environmental events, job strain, and the built environment have been linked to depression, among others [ 52 , 133 , 235 , 236 , 239 , 252 , 269 , 280 , 292 , 293 , 294 , 295 , 296 , 297 , 298 , 299 , 300 , 301 , 302 , 303 , 304 , 305 , 306 , 307 , 308 , 309 , 310 , 311 , 312 , 313 , 314 , 315 , 316 , 317 , 318 , 319 , 320 , 321 , 322 , 323 , 324 , 325 , 326 ,…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies found that the parentā€“child relationship may also be affected by adverse life events (Ren et al, 2019 ), as socioā€economic disadvantages (Malmberg & Flouri, 2011 ), a preterm birth (Candelori et al, 2015 ), serious childhood illness (Pinquart, 2013 ), a parent's serious illness (Babore et al, 2019 ), divorce or separation (Kalmijn, 2013 ) and natural disasters (Dyb et al, 2011 ). Existing research suggested that stressors affect fatherā€“child relationships significantly more than motherā€“child relationships (Almeida et al, 1999 ).…”
Section: Introductionmentioning
confidence: 99%
“…Among participants with a good relationship between parents, the prevalence of depression was only 13%. In contrast, among participants with a bad relationship between parents, the prevalence of depression in their children was 29.2% [45].…”
Section: Family Environment and Only Childmentioning
confidence: 83%